Bertoleza e a servidão escravagista em O Cortiço, de Aluísio de Azevedo - Nogueira, Willianne Marinho (Universidade Federal do Tocantins, 2023)
The focus of this assignment is the life and death representation of the character Bertoleza from the book The Tenement of Aluísio de Azevedo. For more details, this research's corpus consists of two topics, in which the first one revolves around the thought in Literature and how it derives the path in which this character takes and the second is equivalent to reflection about the black body as an object of use and disuse. Based on the point of view of conceptualizations of great model thinkers such as Lélia Gonzalez and Isildinha Nogueira, among others. Thus, we will analyze the path taken by the character and the consequences in which it has been put in regard to its dominators, aiming to analyze the relations of exploitation of the workforce and the expropriation of the character's humanization, with the structure of racism and patriarchy within society and how this action became naturalized about the ungiven black people's dignity. The main indications were that studies like this should be more approached in the classroom as well as in everyday life, as soon as socialization about diversity and interculturality are socially intertwined.